Digital transformations of illicit drug markets : reconfiguration and continuity - Tzanetakis, Meropi; South, Nigel (Emerald Publishing Limited, 2023)
The ebook edition of this title is Open Access and freely available to read online. Transnational illicit markets have been transformed by the digital revolution. They take advantage of encryption technologies, smartphones, social media applications and cryptocurrencies that protect the digital traces of buyers and sellers, posing new challenges to drug control policies and public health alike. Digital Transformations of Illicit Drug Markets: Reconfiguration and Continuity considers how the digital revolution has changed the selling and buying of illicit substances through increased convenience and anonymisation. Providing a uniquely interdisciplinary perspective, chapters show how the digital transformation of illicit drug markets combines a reconfiguration of how sellers and buyers interact in new markets. Emphasising that illicit digital markets are embedded in societal structures and power relations in general, contributors also recognise the importance of critical perspectives on inequalities between the Global North and South as well as issues of gender. Digital Transformations of Illicit Drug Markets: Reconfiguration and Continuity challenges the field of criminology to recognise the limits of its traditional knowledge and move beyond the preoccupations that restrict crime to certain fixed spaces in order to develop new explanations.
Keywords: Drug traffic -- Technological innovations.; Black market.; Computer crimes.; Electronic commerce.; Social Science -- Criminology.; Drugs trade, drug trafficking.; elektronické knihy; electronic books